δ34S character of organosulfur compounds in kerogen and bitumen fractions of sedimentary rocks - Grotheer, H.; Greenwood, P.; McCulloch, M.; Böttcher, M.; Grice, Kliti (Pergamon, 2017)
Hydropyrolysis (HyPy) of S-containing oil mature rock samples from two geologic settings each produced much higher concentrations of organosulfur compounds (OSCs) compared to their free occurrence in the bitumen. The d 34 S values of the most abundant OSCs from the kerogen and in the bitumen, were measured by gas chromatography inductively coupled plasma mass spectrometry (GC-ICP-MS). DBT and mDBTs from the HyPy processed kerogen fractions showed a distinct 34 S depletion, with d 34 S values up to 12‰ lighter than their bitumen occurrence. The different d 34 S values of OSCs from the kerogen and bitumen fractions is likely reflective of differences in timing of production, reduced sulfur sources or organic sulfurisation mechanism.